The impact of mind–body exercise on the quality of life in older adults: the chain mediation effect of perceived social support and psychological resilience - Yang, Qingqing; Zhang, Yinkai; Li, Shiying (Frontiers in Public Health, 2024)
Background: With the intensification of the global aging trend, there is a contradiction between the extended lifespan and the decline of physiological functions among the elderly. It has become a global consensus to focus on and improve the quality of life for the elderly. Mind-body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) play a crucial role in promoting the quality of life for older adults, but the mechanisms and mediating effects are not yet clear. Objective: This study examines the impact of mind-body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) on the quality of life in older adults, with a particular focus on exploring the chain mediating effects of perceived social support and psychological resilience. Results: The study results show that mind-body exercises (Tai Chi, Ba Duan Jin, Yi Jin Jing) are significantly and positively correlated with the quality of life in older adults (r = 0.549, p < 0.01). The path coefficients for the relationships mind-body exercise → perceived social support (β = 0.46, p < 0.001) → psychological resilience (β = 0.20, p < 0.001) → quality of life in older adults (β = 0.39, p < 0.001) are significant, indicating that perceived social support and psychological resilience have a chain mediating effect between mind-body exercise and the quality of life in older adults. Conclusion: Mind-body exercises not only improve the quality of life for older adults but also indirectly enhance it by strengthening perceived social support and psychological resilience. This study provides significant reference for developing health intervention strategies targeted at older adults, suggesting that promoting mind-body exercises can improve their sense of perceived social support and psychological resilience, thereby increasing their quality of life.